DEVELOPMENT OF BRANCH SYSTEM OF CERTIFICATION OF SOFTWARE AND INFORMATION MEANS OF SCIENTIFIC AND EDUCATIONAL PURPOSE - A.J. Sergeev (Kherson State University, 2010)
The article describes the development and implementation of regulatory, organizational, scientific methods of industry certification, the concept of creating software and tools support certification.